2015
DOI: 10.3390/ijms161025377
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-214 and MicroRNA-126 Are Potential Biomarkers for Malignant Endothelial Proliferative Diseases

Abstract: Malignant endothelial proliferative diseases including human angiosarcoma (AS) and canine hemangiosarcoma (HSA) are serious diseases with a grave prognosis. Establishing liquid biopsy-based biomarkers for screening has definite clinical utility; however, plasma miRNAs up- or down-regulated in these sarcomas have been unclear. For identifying possible diagnostic plasma miRNAs for these sarcomas, we investigated whether plasma miR-214 and miR-126, which miRNAs play important roles in angiogenesis and tumorigenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 23 publications
(35 reference statements)
0
38
1
2
Order By: Relevance
“…Both the study reported here and the previously published works had relatively small sample numbers, and evaluation of a larger sample size may help to clarify these confounding results [84, 85]. Despite the lack of agreement in the findings of mir-214, the results reported here agree with the findings of mir-126 reported by the previous group, in which they found overexpression of mir-126 in plasma samples of canine patients with hemangiosarcoma [85]. These previous studies only evaluated mir-214 and mir-126 expression and did not evaluate for other miRNAs, but the finding of mir-126 overexpression, similar to the findings of the current study, is noteworthy.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Both the study reported here and the previously published works had relatively small sample numbers, and evaluation of a larger sample size may help to clarify these confounding results [84, 85]. Despite the lack of agreement in the findings of mir-214, the results reported here agree with the findings of mir-126 reported by the previous group, in which they found overexpression of mir-126 in plasma samples of canine patients with hemangiosarcoma [85]. These previous studies only evaluated mir-214 and mir-126 expression and did not evaluate for other miRNAs, but the finding of mir-126 overexpression, similar to the findings of the current study, is noteworthy.…”
Section: Discussionmentioning
confidence: 81%
“…Later work by the same group found overexpression of mir-214 in the media of canine hemangiosarcoma and human angiosarcoma cell lines, which contradicted their previous findings of underexpression within the cells themselves [85]. They also found increased expression of mir-214 in the plasma of canine patients with hemangiosarcoma, which decreased after tumor removal [85]. The explanation for the contradictory findings in these studies was that intracellular and extracellular concentrations of miRNAs can be different and because miRNAs can have a multitude of downstream targets, they may act differently depending on their location and the disease state.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations